MODELING OF HUMAN CASPASE-5 PROTEIN AND DOCKING STUDIES OF CASPASE-5 INHIBITORS AGAINST MODELED CASPASE-5 - Haripriya Munipalli (Journal of Global Pharma Technology, 2010)
The present study is aimed at building human caspase-5 protein structure by homology modeling. Human interleukin-1 beta convertase P20 (1RWN) and human caspase-1 (3E4C) crystal structures from blast results were taken as caspase-5 structural relatives (from protein data bank). The former showed 58% and the latter, 57% sequence identity with the target caspase-5 protein. The 3D-model was generated by using modeler in Accelrys discovery studio 2.5. The energy refinement was also been carried out in the modeler protocol. The Ramachandran plot showed 89.1% of residues in the favorable region. Further, binding site analysis was done to decipher the interacting residues at the active site region of the modeled protein. Then, docking of Pyrazinone mono amide analogues, peptide aldehydes, substituted P4 aryl sulfonamides on a pyridine scaffold analogues, P1 aspartyl ketone derivatives on a pyridine scaffold analogues and a P3 sulfonamide-modified thiophene derivatives against modeled human caspase-5 protein were performed using ligandFit. The results showed that Cys161, Arg55, Val214 and His113 were found to be among the interacting residues of caspase-5 with all the types of inhibitors. These 4 residues of caspase-5 active site were found to be interacting with the crystal ligand (copied from 1RWN) also. The dock scores of P4 aryl sulfonamides on pyridine scaffold analogues and P1 Aspartyl Ketone derivatives on Pyridine Scaffold analogues were higher indicating their high activity against caspase-5 compared to that of pyrazinone monoamide analogues and tetra peptides.Keywords: 1RWN; 3E4C; Ligand Fit; Human Caspase-5; Homology Modeling; Ramachandran Plot